Bacteriophage-Antibiotic Combination Therapy against Pseudomonas aeruginosa - Guillermo Santamaría-Corral; Abrar Senhaji-Kacha; Antonio Broncano-Lavado; Jaime Esteban; Meritxell García-Quintanilla (MDPI AG, 2023)
Phage therapy is an alternative therapy that is being used as the last resource against infections caused by multidrug-resistant bacteria after the failure of standard treatments. Pseudomonas aeruginosa can cause pneumonia, septicemia, urinary tract, and surgery site infections mainly in immunocompromised people, although it can cause infections in many different patient profiles. Cystic fibrosis patients are particularly vulnerable. In vitro and in vivo studies of phage therapy against P. aeruginosa include both bacteriophages alone and combined with antibiotics. However, the former is the most promising strategy utilized in clinical infections. This review summarizes the recent studies of phage-antibiotic combinations, highlighting the synergistic effects of in vitro and in vivo experiments and successful treatments in patients.